The Role of Board Oversight in Central Bank Governance : Key Legal Design Issues - Bossu, Wouter (IMF Working Papers; Working Paper ;, 2019)
This paper discusses key legal issues in the design of Board Oversight in central banks. Central banks are complex and sophisticated organizations that are challenging to manage. While most economic literature focuses on decision-making in the context of monetary policy formulation, this paper focuses on the Board oversight of central banks-a central feature of sound governance. This form of oversight is the decision-making responsibility through which an internal body of the central bank-the Oversight Board-ensures that the central bank is well-managed. First, the paper will contextualize the role of Board oversight into the broader legal structure for central bank governance by considering this form of oversight as one of the core decision-making responsibilities of central banks. Secondly, the paper will focus on a number of important legal design issues for Board Oversight, by contrasting the current practices of the IMF membership's 174 central banks with staff's advisory practice developed over the past 50 years.